Rotavirus Induces Epithelial–Mesenchymal Transition Markers by Transcriptional Suppression of miRNA-29b - Mukhopadhyay, Urbi; Banerjee, Anwesha; Chawla-Sarkar, Mamta; Mukherjee, Anupam (Frontiers in Microbiology, 2021)
Acute gastroenteritis (AGE) is a serious global health problem and have been known to cause millions of infant deaths every year. Rotavirus (RV), a member of the Reoviridae family, still majorly accounts for the acute gastroenteritis in children below 5 years of age in India and worldwide. The involvement of miRNAs in the pathogenesis of rotavirus have been suggested to be of the pro-viral as well as the anti-viral nature. miRNAs that promote the rotavirus pathogenesis are capable of targeting the cellular components to evade the host anti-viral strategies. On the other hand, miRNAs with anti-rotaviral properties are themselves incapacitated during the progression of the infection. The exploitation of the Epithelial-Mesenchymal Transition (EMT) as a pro-rotaviral strategy has already been identified. Thus miRNAs that proficiently target the intermediates of the EMT pathway may serve as anti-viral counterparts in the RV-host interactions. The role of microRNA-29b (miR-29b) in the majority of human cancers has been well demonstrated but its significance in viral infections is yet to be elaborated. In this study, we have assessed the role of miR-29b in rotavirus induced Epithelial-Mesenchymal Transition and RV replication. Our study on miR-29b provides evidence for the recruitment of RV non-structural protein NSP1 to control the trans-repression of miR-29b in a p53-dependent manner. The trans-repression of miR-29b modulates the EMT pathway by targeting TRIM44 and CCNE1. SLUG and SNAIL transcription repressors (downstream of TRIM44 and CCNE1) regulates the expression of E-cadherin, an important marker of the EMT. Also, it is established that ectopic expression of miR-29b not only constrains the EMT pathway but also restricts RV replication. Therefore, miR-29b repression is a crucial event in the RV pathogenesis. Ectopic expression of miR-29b displays potential antiviral properties against RV propagation.